2021
DOI: 10.14715/cmb/2021.67.2.23
|View full text |Cite
|
Sign up to set email alerts
|

The anti-fatigue potential of water-soluble polysaccharides of Semen cassiae on BALB/c mice

Abstract: Fatigue syndrome is a major health problem that affects the voluntary activities of an individual. Particularly, exercise-induced fatigue has become a serious concern in people's health. Since polysaccharides from various medicinal plants have been reported for anti-fatigue effect, the current study deals with the anti-fatigue potential of water-soluble polysaccharides of the Chinese medicinal plant Semen cassiae (Cassia obtusifolia L.) in BALB/c mice. Water-soluble polysaccharides from Semen cassiae were extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
(36 reference statements)
1
7
0
Order By: Relevance
“…In an experiment involving the forced swimming of mice, it was shown that LBP1-decorated selenium nanoparticles (LBP1-SeNPs) were able to mitigate fatigue by increasing the reserve of glycogen in the liver and muscles [ 79 ]. This result was consistent with most other findings [ 14 , 17 , 70 ]. Importantly, adenosine 5‘- monophosphate-activated protein kinase (AMPK) is a master regulator that senses the energy state, maintains glucose homeostasis, and mediates beneficial cellular adaptations in many vital tissues and organs [ 83 ].…”
Section: Polysaccharides Ameliorate Fatiguesupporting
confidence: 94%
See 2 more Smart Citations
“…In an experiment involving the forced swimming of mice, it was shown that LBP1-decorated selenium nanoparticles (LBP1-SeNPs) were able to mitigate fatigue by increasing the reserve of glycogen in the liver and muscles [ 79 ]. This result was consistent with most other findings [ 14 , 17 , 70 ]. Importantly, adenosine 5‘- monophosphate-activated protein kinase (AMPK) is a master regulator that senses the energy state, maintains glucose homeostasis, and mediates beneficial cellular adaptations in many vital tissues and organs [ 83 ].…”
Section: Polysaccharides Ameliorate Fatiguesupporting
confidence: 94%
“…Polysaccharides have been considered to be a new natural and effective anti-fatigue substance [ 9 ]. Some natural polysaccharides, such as Semen cassiae ( Cassia obtusifolia L.) [ 14 ], Ganoderma lucidum [ 15 ], Lycium barbarum [ 68 ], Cordyceps militaris [ 69 ], and apple pomace [ 70 ], exert beneficial anti-fatigue effects via different pathways ( Figure 1 ). The monosaccharide composition and the anti-fatigue mechanisms of natural polysaccharides are summarized in Table 1 .…”
Section: Polysaccharides Ameliorate Fatiguementioning
confidence: 99%
See 1 more Smart Citation
“…Plasma levels of LD, LDH, and BUN were determined by the instruction of corresponding kits. 15,16 The liver and gastrocnemius of mice were also taken to determine the content of liver glycogen and muscle glycogen. All parameters were tested following the recommended procedures by the manufacturers of the respective kits.…”
Section: Papermentioning
confidence: 99%
“…In recent years, the application of natural products in nutritional intervention for fatigue has attracted increased attention [ 1 ]. Anti-fatigue active substances such as polypeptides [ 16 ], polysaccharides [ 17 , 18 ], and proteins [ 19 ] are characterized by high safety, no side effects, and significant efficacy. Therefore, using natural active ingredients to develop natural functional products has become an urgent need in the market.…”
Section: Introductionmentioning
confidence: 99%